Microstructural evolution during multiple scans in laser polishing of Ti6Al4V. (March 2022) - Zhou, Jing; Shen, Hong; Lin, Yiwei; Liao, Conghao; Yu, Qinghua
Abstract: Consecutive thermal cycles during laser polishing lead the complex microstructural changes. It is more difficult for modeling microstructural evolution in multiple thermal cycles compared to the single thermal cycle of heat treatment. In the present work, a thermo-microstructural model is established to investigate the temperature history and microstructural evolution during multiple scans in laser polishing of Ti6Al4V (TC4). The temperature history of the present model is validated the temperature data recorded by the thermal camera. The phase transformation involved α phase and β phase, martensitic transformation and decomposition, as well as the reservation of β phase is considered in the microstructural model. The numerical results show that the non-uniform phase distribution is attributed to the reservation of β phase and the multiple thermal cycles.